Climate Change and Emotions: Analysis of People’s Emotional States in Southern Ecuador - Iniguez-Gallardo, Verónica; Lenti Boero, Daniela; Tzanopoulos, Joseph (Frontiers in Psychology, 2021)
Climate change involves multiple emotional expressions associated with specific labels, notably: ‘concern’ ‘guilt’, or ‘scepticism’ However, there are other types of emotions that have been less analysed, such as ‘powerlessness’, ‘anger’ and ‘confusion’ that are of equal importance for predicting behavioural changes towards this climatic issue. Likewise, few studies in this research field rely on qualitative data to understand and identify the causative agents for the emotional arousal. This research explores a range of emotions, mixing those that have been widely studied and those that have been hardly analysed. It also looks at the demographic parameters associated with such emotions using a population sample from southern Ecuador. The study analyses quantitative and qualitative data gathered through structured-questionnaires whereby participants were given agency to select and define how they themselves sense emotionally climate change. The results indicate that two of the five participants' most selected emotions are shared with other nations (‘concern’, ‘guilt’), while the other three have been less reported and studied in the climate change field (‘powerlessness’, ‘anger’, and ‘confusion’). These emotions were found to be aroused by different reasons associated with specific demographic variables. The findings reveal the role of the cultural and local environment in the emotional arousal and its relevance for designing more effective climate communication campaigns.